Structural brain differences in emotional processing and regulation areas between male batterers and other criminals: A preliminary study. (4th July 2019) - Verdejo-Román, Juan; Bueso-Izquierdo, Natalia; Daugherty, Julia C.; Pérez-García, Miguel; Hidalgo-Ruzzante, Natalia
ABSTRACT: Poor emotion processing is thought to influence violent behaviors among male batterers in abusive relationships. Nevertheless, little is known about the neural mechanisms of emotion processing in this population. With the objective of better understanding brain structure and its relation to emotion processing in male batterers, the present study compares the cortical grey matter thickness of male batterers to that of other criminals in brain areas related to emotion. Differences among these brain areas were also compared to an emotional perception task. An MRI study and an emotional perception assessment was conducted with 21 male batterers and 20 men convicted of crimes other than Intimate Partner Violence (IPV). Results demonstrated that batterers' had significantly thinner cortices in prefrontal (orbitofrontal), midline (anterior and posterior cingulate) and limbic (insula, parahipocampal) brain regions. The thickness of the dorsal posterior cingulate cortex in the batterer group correlated with scores on the emotional perception task. These findings shed light on a neuroscientific approach to analyzing violent behavior perpetrated by male batterers, leading to a better understanding of the underlying mechanisms involved in IPV.